Pas de quartier pour le sexe ? - Catherine Deschamps; Laurent Gaissad (EchoGéo)
This article proposes to analyse different spaces dedicated to sexual cruising and encounters, and the way social sciences have sometimes neglected certain forms of sexual desire, in particular regarding gender and sexual identity. Grounded on three fieldwork surveys on sex work, men-to-men cruising for sex, and men and women sexual sociability venues, it outlines the way sexual territories seem to be under control at first sight, and tries to show that sexual conducts alternatively appear spectacular or remain invisible, both in material public spaces and in contemporary debates, including academic research.